Lsh, an SNF2/helicase family member, is required for proliferation of mature T lymphocytes - Geiman, T. M. (The National Academy of Sciences, 2000)
Lsh (Hells) is closely related to SNF2/helicase family members that remodel chromatin and thus regulate gene transcription. In the adult mouse Lsh is expressed primarily in lymphoid tissue, showing the highest level in thymocytes. Lsh gene expression can be induced in thymic pro-T cells by pre-T cell receptor crosslinking and in mature T cells by T cell receptor crosslinking together with costimulation via CD28. The time course of Lsh gene and protein expression correlated closely with the onset of S phase of the cell cycle. To explore the function of Lsh during lymphoid development or activation, we deleted the Lsh gene by homologous recombination in ES cells. Fetal liver cells from Lsh−/− were used as a source of hematopoietic precursors to reconstitute lymphoid development in Rag2−/− mice. Lsh−/− (compared to Lsh+/+ or ±) chimeras showed a modest reduction in thymocyte numbers due to a partial arrest at the transition from the CD4(−)CD8(−) stage to the CD4(+)CD8(+) stage of T cell development. Mature peripheral lymphocytes were reduced in number to ≈60% for T cells and 40% for B cells; however, V(D)J recombination of the immune receptor genes was normal. Although polyclonal activation of Lsh−/− T cells induced normal levels of cytokines, cell proliferation was severely suppressed and cells underwent apoptosis. Several genes involved in the regulation of apoptosis were expressed normally with the exception of Bcl-2 that was actually elevated. These findings demonstrate that Lsh is not obligatory for normal lymphoid development but is essential for normal proliferation of peripheral T lymphocytes.